Penggunaan Papan Bacaan Arab Braille dalam Upaya Meningkatkan Kemampuan Mengenal Huruf Hijaiyah Arab Braille Bagi Tunanetra - Vanni Alfionita; Irdamurni Irdamurni (Universitas Muhammadiyah Enrekang, 2022)
This research was motivated by the existence of problems in class XI blind children at SMK N 7 Padang, who experienced problems in recognizing braille arabic hijaiyah letters where children did not know and had never studied or were taught about braille arabic hijaiyah letters. Based on the problem above, this study aims to prove that media braille arabic reading can be used to introduce braille arabic hijaiyah letters to blind children. The design used in this study is the A-B-A design with the single subject research (SSR) method and the target behavior is remembering and writing the braille hijaiyah letters from Alif (١) – Ya (ﻱ). The results of this study indicate that media arabic braille reading board can be used to introduce braille arabic hijaiyah letters to blind children. In the analysis in conditions with the number of variables analyzed with the results of the analysis of the tendency of stability in condition (A1) 0%, (B) +11,11% and (A2) +100%. In the analysis between conditions in the from of Percentage of overlape in the baseline condition (A1) with the intervention condition at 0% and in the baseline condition after the intervention (A2) with the intervention condition at 44,44%. The number 100% proves that the hypothesis is accepted and media arabic braille reading board can be used in introducing the arabic braille hijaiyah letters.